Contraceptive use and unplanned pregnancy among female sex workers in Zambia - Chanda, Michael M.; Bärnighausen, Till (Contraception, 2017)
Objectives Access to reproductive healthcare, including contraceptive services, is an essential component of comprehensive healthcare for female sex workers (FSW). Here, we evaluated the prevalence of and factors associated with contraceptive use, unplanned pregnancy, and pregnancy termination among FSW in three transit towns in Zambia.Study design. Data arose from the baseline quantitative survey from a randomized controlled trial of HIV self-testing among FSW. Eligible participants were 18 years of age or older, exchanged sex for money or goods at least once in the past month, and were HIV-uninfected or status unknown without recent HIV testing (<3 months). Logistic regression models were used to assess factors associated with contraceptive use and unplanned pregnancy. Results Of 946 women eligible for this analysis, 84.1% had been pregnant at least once, and among those 61.6% had an unplanned pregnancy, and 47.7% had a terminated pregnancy. Incarceration was associated with decreased odds of dual contraception use (aOR=0.46, 95% CI 0.32-0.67) and increased odds of unplanned pregnancy (aOR=1.75, 95% CI 1.56-1.97). Condom availability at work was associated with increased odds of using condoms only for contraception (aOR=1.74, 95% CI 1.21-2.51) and decreased odds of unplanned pregnancy (aOR=0.63, 95% CI 0.61-0.64).Conclusions FSW in this setting have large unmet reproductive health needs. Structural interventions, such as increasing condom availability in workplaces, may be useful for reducing the burden of unplanned pregnancy.